Editorial Introduction - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2009)
As the editor for Networks, I often get questions from authors and reviewers about what we look for in high-quality submissions. In this column, I identify some of the criteria that we consider as we make decisions about sending articles out to reviewers and contemplate publication. Networks publishes three types of peer-reviewed submissions: full-length articles, shorter articles, and book reviews.